Deliberative Visioning: A Critical View Observations From a Scenario Workshop for Water Management in a Greek Island - Harry Coccossis; Dionisia Hatzilakou; Alexandra Mexa; Eleni Svoronou; Giorgos Kallis (European Regional Science Association (ERSA), 2006)
There is a growing policy interest in participatory processes that combine deliberation with futures visioning. The EU Water Framework Directive, with its mandate for participatory long-term river basin plans, contributes to this "futures turn" in European governance. In this paper we investigate what Deliberative Visioning can do well and what not in the context of resource planning. Our laboratory is a Scenario Workshop for sustainable water management in a Greek island. We conclude that Deliberative Visioning is useful for preparatory and complementary planning activities such as education, community motivation, communication and consultation but it is not well suited for action planning per se. Visions are not substantive decision outputs or bases for a participatory policy options assessment, but effective devices for communication and mutual learning between participants. Our study touches also some broader issues concerning the interface of participation/deliberation, science and decision-making.
Keywords: 330